Biological activity of gold nanoparticles combined with the NFL-TBS.40-63 peptide, or with other cell penetrating peptides, on rat glioblastoma cells - A. Griveau; C. Arib; J. Spadavecchia; J. Eyer (Elsevier, 2022)
Targeting, detecting, and destroying selectively cancer cells or specific organelles is a major challenge of nanomedicine. Recently, a new methodology was conceived to synthesize gold nanoparticles combined with a peptide having a C-terminal biotin (BIOT-NFL-peptide). This methodology called "Method IN" allows specific interactions between the BIOT-NFL-peptide, the polyethylene glycol diacid (PEG-COOH) and the gold salt (Au III) to produce multifunctional hybrid nano-carriers called BIOT-NFL-PEG-AuNPs. Here, we show that it is possible to use this strategy to synthesize multifunctional hybrid nano-carriers with other cell-penetrating peptides including TAT and Vim-peptides. Ex-vivo studies on F98 rat glioblastoma cells show that these new nanovectors acquire the cellular entry function of peptides and the gold particles make it possible to visualize by electron microscopy their localization in organelles. Thus, these new multifunctional nanovectors offer promising possibilities for the theranostic field, including the cell-penetrating property of the peptide, the intra-organelle localization of gold particles and their possible thermoplasmonic properties, as well as the stealth property of PEG.